Design modification of the existing cooling water system of Marsyangdi hydropower station using pipe flow modeling software - Bista, Prabhab; Ghimire, Subodh Kumar; Sapkota, Rama (Journal of Innovations in Engineering Education, 2022)
Marsyangdi Hydropower Station has adopted the Open Loop Cooling System (also called Once through Cooling System) in which the cooling water extracted from Penstock or the draft tube is circulated throughout the cooling system and discharged back to the draft tube. The water of the Marsyangdi River is muddy and sediment-rich in the rainy season, which causes the choking of tubes of the primary heat exchangers reducing the cooling efficiency and even leading to leakages in the tubes due to erosion. Cleaning and maintenance of the tubes are impossible without dismantling the primary heat exchangers from the Unit assembly. Hence, hours of machine shutdown is required to replace them with new or cleaned one. A Close Loop Cooling System has been modeled in the Software, "AFT Fathom," to overcome the issue in the Existing Cooling System. The modified model was run to observe the performance of the modified system at different river water temperatures and increased heat duty in all the heat exchangers. Further, the System Curve was considering the effect of the increase in surface roughness of pipelines due to aging. The performance capacity of the modified system was justified considering the obtained results from the simulations.